Ligularia muliensis (Asteraceae, Senecioneae) is merged with L. tsangchanensis - Illarionova, Irina; Wang, Long; Yang, Qin-Er (Phytotaxa, 2017)
Observations on both herbarium specimens (including type material) and living plants demonstrate that Ligularia muliensis and L. tsangchanensis are conspecific. We therefore place L. muliensis into the synonymy of L. tsangchanensis. Lectotypfications are proposed for L. tsangchanensis and L. muliensis.